Effect of U(VI) aqueous speciation on the binding of uranium by the cell surface of Rhodotorula mucilaginosa, a natural yeast isolate from bentonites. (May 2018) - Lopez-Fernandez, Margarita; Romero-González, Maria; Günther, Alix; Solari, Pier L.; Merroun, Mohamed L.
Abstract: This study presents the effect of aqueous uranium speciation (U-hydroxides and U-hydroxo-carbonates) on the interaction of this radionuclide with the cells of the yeast Rhodotorula mucigilanosa BII-R8. This strain was isolated from Spanish bentonites considered as reference materials for the engineered barrier components of the future deep geological repository of radioactive waste. X-ray absorption and infrared spectroscopy showed that the aqueous uranium speciation has no effect on the uranium binding process by this yeast strain. The cells bind mobile uranium species (U-hydroxides and U-hydroxo-carbonates) from solution via a time-dependent process initiated by the adsorption of uranium species to carboxyl groups. This leads to the subsequent involvement of organic phosphate groups forming uranium complexes with a local coordination similar to that of the uranyl mineral phase meta-autunite. Scanning transmission electron microscopy with high angle annular dark field analysis showed uranium accumulations at the cell surface associated with phosphorus containing ligands. Moreover, the effect of uranium mobile species on the cell viability and metabolic activity was examined by means of flow cytometry techniques, revealing that the cell metabolism is more affected by higher concentrations of uranium than the cell viability. The results obtained in this work provide new insights on the interaction of uranium with bentonite natural yeast from genus Rhodotorula under deep geological repository relevant conditions. Graphical abstract: Image 1 Highlights: Rhodotorula mucilaginosa BII-R8 cells are involved in the biosorption of uranium. Yeast cells bind mobile uranium species from solution via a time-dependent process. Carboxyl groups at the cell surface attract U-hydroxides and U-hydroxo-carbonates. Formed uranium species interact with organic phosphate groups at the cell wall. Uranium complexes have a similar local coordination to that of meta-autunite.